The Forkhead Transcription Factor FOXP2 Is Required for Regulation of p21(WAF1/CIP1) in 143B Osteosarcoma Cell Growth Arrest - Gascoyne, Duncan M. (PLoS One, 2015)
Mutations of the forkhead transcription factor FOXP2 gene have been implicated in inherited speech-and-language disorders, and specific Foxp2 expression patterns in neuronal populations and neuronal phenotypes arising from Foxp2 disruption have been described. However, molecular functions of FOXP2 are not completely understood. Here we report a requirement for FOXP2 in growth arrest of the osteosarcoma cell line 143B. We observed endogenous expression of this transcription factor both transiently in normally developing murine osteoblasts and constitutively in human SAOS-2 osteosarcoma cells blocked in early osteoblast development. Critically, we demonstrate that in 143B osteosarcoma cells with minimal endogenous expression, FOXP2 induced by growth arrest is required for up-regulation of p21(WAF1/CIP1). Upon growth factor withdrawal, FOXP2 induction occurs rapidly and precedes p21(WAF1/CIP1) activation. Additionally, FOXP2 expression could be induced by MAPK pathway inhibition in growth-arrested 143B cells, but not in traditional cell line models of osteoblast differentiation (MG-63, C2C12, MC3T3-E1). Our data are consistent with a model in which transient upregulation of Foxp2 in pre-osteoblast mesenchymal cells regulates a p21-dependent growth arrest checkpoint, which may have implications for normal mesenchymal and osteosarcoma biology.